2020
DOI: 10.1021/acsami.0c02566
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Smart Textile Derived from Merino Wool/Nylon Polymer Nanocomposites as Next Generation Microwave Absorber and Soft Touch Sensor

Abstract: In recent times e-textiles have emerged as wonder safeguards due to the great potential background in space, military, healthcare, or portable electronics. As a result, widespread research and development have been done to make significant advancement in this field, but it still remains a key challenge to use one single product with multifunctional attributes with the past performance of key characteristics. In this work, phase-separated PEDOT:PSS ornamented with reduced graphene oxide (rGO) nanosheets, deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 44 publications
0
46
0
Order By: Relevance
“…23 Electroconducting cellulose-based bers have been developed as excellent candidates for a wide range of innovative applications in the elds of organic electronics, sensors, antistatistic materials, electromagnetic inductive inductor harnessing, heating, and energy storage systems. 24 When compostable or incinerated with energy for recycling at the end of their life cycle, they have the benets of being plentiful, sustainable, biodegradable, and carbon dioxide free. It takes little energy for their processing and their waste stream is recyclable and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…23 Electroconducting cellulose-based bers have been developed as excellent candidates for a wide range of innovative applications in the elds of organic electronics, sensors, antistatistic materials, electromagnetic inductive inductor harnessing, heating, and energy storage systems. 24 When compostable or incinerated with energy for recycling at the end of their life cycle, they have the benets of being plentiful, sustainable, biodegradable, and carbon dioxide free. It takes little energy for their processing and their waste stream is recyclable and biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…Through adding electronic elements, e-textiles such as conductive fibers or fabrics can use in wearable devices, human-machine interface, or controlling/monitoring applications [84,85]. One kind of the dip-coated multifunctional textiles has been completed by uniform deposition of poly(3,4-ethylenedioxythiophene) (PEDOT) clusters and a stacked layer of PEDOTs/rGO-PEDOTs/PEDOTs within the wool/nylon textile surface [86]. As a result, the soft-touch textile sensors (Figure 3c diode.…”
Section: E-textiles-based Approachmentioning
confidence: 99%
“…[ 109 ] In another work same group has reported multifunctionality of nylon‐based CPC as microwave absorber along with soft touch sensors. [ 113 ] All the stimuli responsive change in electrical conductivity of CPC make them suitable candidate not only for VOC and strain sensor but also for other smart applications like stretchable and flexible conductor, [ 114 ] electronic skin, [ 115 ] smart textile material, [ 116 ] surface protection materials, membrane for gas separation, [ 117 ] and so on. It can be concluded that CPC has tremendous application regime owing to their lightweight, tunable electrical and mechanical properties, and ease of production, which is perfectly compatible with industrial adaptation, and low cost.…”
Section: Application Domains Of Cpcsmentioning
confidence: 99%